Effect of glycerol on catalysis by low molecular weight acid phosphatase from alpaca liver (Lama pacos) - Guija, Emilio (2007)
Objective: To determine the effect of glycerol on hydrolisis of p-nitrophenyl phosphate at pH 5,0 by low molecular weight acid phosphatase from alpaca liver. Design: Experimental analytical study. Setting: Biochemistry and Nutrition Research Center, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Materials: Disodic p-nitrophenyl phosphate salt, glacial acetic acid, glycerol, tricloroacetic acid, sulfuric acid, ammonium molibdate, ascorbic acid, ammonium sulphate, sephadex G-75 (45-120), sulpho ethyl sephadex C-50 and ethylene diaminotetraacetic (EDTA) chemical reactives. Methods: Both Km and Vmax kinetic parameters were determined with p-nitrophenyl phosphate as substrate in presence of different concentrations of glycerol. The rate of formation of products was determined as a function of the concentration of such nucleophile. Main outcome measures: Glycerol effect on p-nitrophenyl phosphate hydrolysis. Results: Glycerol linearly increased pnitrophenol release at concentrations between 1,16 and 3,49M. Instead, inorganic phosphate formation, the second product, was not modified. Also, Km and Vmax values increased linearly between 0,58 and 2,32 M depending on glycerol concentrations. Conclusions: Analysis of modifications induced by glycerol on Km and Vmax values as well as on liberation velocity of the reaction products suggests a model in which low molecular weight acid phosphatase isolated from alpaca liver catalyses phosphomonoesters hydrolysis through an uni biordered mechanism, with formation of an enzyme-phosphate complex that will be splitted by water or a nucleophile such a glycerol; in this model, k2 corresponds to a much higher value than k3 or k4 N.